Réponses

2013-12-17T22:49:00+01:00
-3x-5x=2+7
-8x=9
x=-8/9

5x/2-2x/3-x/3=-5/3                                               -(x-7)(5x+2)=0
5x/2-3x/3=-5/3                                                     -(5x²+2x-35x-14)=0
5x/2-x=-5/3                                                           -5x²-2x+35x+14=0
3x/2=-5/3                                                              -5x²+33x+14 =0
9x=-10
x=-10/9
2x/3+5x/2 = x/3-5/3
x/3-5x/2=-5/3
-13x/6=-5/3
x=30/39 =10/13
(x-7)(5x+2) = 5x²+2x-35x-14 =5x²-33x-14
2013-12-17T23:56:08+01:00